Application of Microneedles for High-Molecular-Weight Dextran Penetration Across the Buccal Mucosa - Adriana Fantini; Andrea Delledonne; Luca Casula; Sara Nicoli; Silvia Pescina; Maria Cristina Cardia; Francesco Lai; Cristina Sissa; Patrizia Santi; Cristina Padula (Pharmaceuticals)
Objectives: This work aimed at investigating the effect of different microneedle-based strategies on the permeation of high-molecular-weight model molecules (fluorescently labeled dextrans (FDs), 70 and 150 kDa) across the buccal mucosa. Methods: Two different approaches were evaluated: (1) stainless steel microneedles (MNs) of 500 µm height used for tissue pre-treatment; and (2) soluble microneedles of different lengths (150, 500, and 800 µm), made of polyvinylpyrrolidone and FDs, prepared using the solvent casting technique. Porcine esophageal epithelium was used as a model for the buccal mucosa. Results: The application of soluble MNs promoted high-molecular-weight dextran transport across pig esophageal epithelium. The transport was proportional to MN length, with a minimum of 500 µm, regardless of the molecular weight of the FDs. The use of solid MNs of the same length to pre-treat the tissue, followed by the application of a solution of the permeant, did not produce the same effect in terms of onset of permeation, which was found to be much slower. Conclusions: The results obtained show that by applying soluble MNs of appropriate length (500 and 800 µm), the transport of high-molecular-weight dextrans (70 and 150 kDa) across and into the mucosal tissue occurs very rapidly. The multiphoton microscopy analysis confirmed the presence of holes in the tissue and the presence of fluorescein-labeled dextrans.